Analisis Nilai Keausan pada Lapis Hot Rolled Sheet (HRS) dengan Menggunakan Reclaimed Asphalt Pavement (RAP) dan Styrofoam - Alfian Saleh; Dapot Syaloom Harianja; Fadrizal Lubis (JURNAL TEKNIK UNILAK, 2022)
The application of recycling using Reclaimed Asphalt Pavement (RAP), where Reclaimed Asphalt Pavement (RAP) is a road structure rehabilitation concept, by optimizing the reuse of old materials into new pavement materials. In this study, materials from Reclaimed Asphalt Pavement were used for the Hot Rolled Sheet (HRS) layer by utilizing added material in the form of Styrofoam waste material. Styrofoam has the same properties as asphalt, namely thermoplastic which is one of the reasons it is used as an added material. From the results of the KAO test, it was made with a value variation of 6.2%; 6.7%; 7.2%; 7.7%; 8.2% and obtained the optimum asphalt content value of 7.24%. From the optimum asphalt content obtained, it is continued by searching for the optimum styrofoam content. The search for optimum styrofoam content was carried out using the addition of various values of 0%, 6%, 12%, 18%, 24% of the asphalt weight. Where all test results meet the 2018 Highways specifications with the highest stability value of 3,688.87 kg and optimum styrofoam content of 17.218%. After getting the optimum asphalt and styrofoam content, the cantabro test was carried out with an average weight loss value of 3.81%. The results of this study indicate that the use of Reclaimed Asphalt Pavement (RAP) material added with Styrofoam on the Hot Rolled Sheet pavement layer has a high resistance to wear and tear.